The Tides of Peace - Robertson, Denise (London Little Books, 2010)
"The story of three women linked by fate and war and the men who loved or hated them. It is 1945 and men and women prepare to return to the lives they left behind in 1939. But the world, for most of them, has changed beyond recognition."--Publisher's description.
Keywords: Social classes -- World War (1939-1945) -- Great Britain